PENEGAKAN HUKUM BERBASIS KEADILAN RESTORATIF JUSTICE TERHADAP ANAK KORBAN NARKOTIKA - Sri Wahyuni Ginting, Syahrul Bakti Harahap (NERACA KEADILAN, 2025)
The development of drug cases in Indonesia over the past few decades has shown a very worrying trend. Drug abuse is no longer limited to adults, but has spread to children and adolescents who are psychologically and socially vulnerable. Children who should be the focus of protection and guidance have instead become victims of drug abuse. Restorative Justice is an approach in the criminal justice system that focuses more on restoring relationships between perpetrators, victims, and communities affected by criminal acts, rather than simply punishing the perpetrators. From an international perspective, the Convention on the Rights of the Child (CRC) which has been ratified by Indonesia through Presidential Decree Number 36 of 1990, provides a similar definition that. A child is every human being under the age of 18, unless under the laws applicable to children, adulthood is reached earlier. The type of research used in this study is normative juridical. This study uses a criminological approach with a qualitative method. This approach was chosen to analyze the effectiveness of the implementation of restorative justice in handling child crimes in Indonesia. This study aims to understand the social, legal, and cultural contexts that influence the implementation of restorative justice and its impact on children involved in criminal acts. The implementation of restorative justice faces several obstacles, including the lack of understanding of law enforcement, social stigma against child victims of narcotics, and limited rehabilitation facilities. In addition, existing legal regulations do not fully support the optimal implementation of restorative justice.